Analisis Manajemen Perubahan pada Layanan Administrasi di Disdukcapil Kota Medan - Laila Dwi Ningrum; Chuzaimah Batubara (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Socialization done online improves the quality of socialization. However, adaptability is an important factor in system operation. This is evident from the information on the Sibisha website, the prices of the documents, and the frequent incidents of brokers and robberies in Disdhukhapil, Medan city. Very important in this case to use the highest level of personalization when implementing online services in order to create a quality population control and people registration system. A descriptive qualitative search system was used with the aim of further demonstrating the attractiveness of data collection. The suggestions used are from Stephen P. Robbins and Mary Coulter, who emphasized careful adaptation through changes in strategy, organizational structure, technological advances, and fanatical fanaticism. The results of the study show that Sibisa’s modifications to its administrative and registration procedures in Kota Medan have not yet been successful in achieving their full potential. This is due to the slow socialization of the general populace regarding the use of the Sibisa service, the continual desire to improve product quality pundi-pundi korban, and the long wait times for service technicians to evaluate the quality of online services.